2019
DOI: 10.1021/acscentsci.9b00372
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Challenges in Luminescent Imaging: Bright Outlook for Chemiluminescence of Dioxetanes in Water

Abstract: Chemiluminescence is gradually being recognized as a powerful tool for sensing and imaging. Most known light-emitting compounds undergo chemiexcitation through spontaneous decomposition of cyclic peroxide moieties. A ground-breaking milestone in the chemistry of such compounds was achieved 30 years ago with the discovery of triggerable dioxetanes by Schaap’s group. Our group has recently developed a distinct methodology to significantly improve the light emission efficiency of such phenoxy-dioxetane luminophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 75 publications
(137 reference statements)
1
146
0
4
Order By: Relevance
“…35 The ability to incorporate various releasable functionalities with this approach has great potential in the design of cleavable traceless linkers for antibody drug conjugates, neuromodulator delivery strategies, triggered catalysis and bioimaging. [35][36][37][38][39][40] Thiol/amine associated reactions that concurrently capture the key advantageous features of trigger-torelease and trigger-to-reverse processes are not well-studied. Combining these features offers the opportunity to bring about new functions in areas that are independently represented by both these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…35 The ability to incorporate various releasable functionalities with this approach has great potential in the design of cleavable traceless linkers for antibody drug conjugates, neuromodulator delivery strategies, triggered catalysis and bioimaging. [35][36][37][38][39][40] Thiol/amine associated reactions that concurrently capture the key advantageous features of trigger-torelease and trigger-to-reverse processes are not well-studied. Combining these features offers the opportunity to bring about new functions in areas that are independently represented by both these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, great progression has been achieved for developing new chemiluminescence probes and their application. Most of chemiluminescence probes are dependent on ROS reactions and most of the probes have been used to detect ROS in solutions, cells, and in vivo [11][12][13][14][15][16][17][18] . Surprisingly, we found that ADLumin-1 was much more sensitive to O2 (27-fold change), and the responses were very quick (within seconds).…”
Section: Discussionmentioning
confidence: 99%
“…chemiluminescence, including dioxetane 12,[59][60][61] , luminol 62 , imidazo[1,2-a]pyrazin-3(7H)-one 63 , oxalate [15][16] , lucigenin 62 , 9,10-dimethyl-anthracene 18 , and 10-methyl-9-(phenoxycarbonyl) acridinium 64 . All of these scaffolds have short emission wavelengths (< 500 nm) and are not ideal for in vivo imaging, particularly for deep locations such as brains.…”
Section: Design and Synthesis Of Adlumin-several Scaffolds Have Been mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemiluminescence, a phenomenon of light radiation accompanied by chemical reactions, has been increasingly recognized as a powerful tool for disease diagnosis and biological analysis. [100][101][102] Compared to traditional uorescence imaging, CLI has the advantages of high sensitivity, low phototoxicity, and high signal-to-noise ratio due to the removal of the external excitation source. Peroxalate derivatives working as lightemitting functionalities have been widely explored for chemiluminescence.…”
Section: Chemiluminescence Imaging-guided Pdtmentioning
confidence: 99%